Metastatic tumor in the breast: primitive: gastric cancer - Estrugo, Roberto L; Iraola, María L; Beriao, Juan C; Perrone, Luis (Cirugía del Uruguay, 1975)
A case is described of metastatic cancer of the breast, secondary to a gastric adenocarcinoma, coinciding with a scirrhous carcinoma of the opposite breast ( first case published in our country). The histopathological coincidence between the primary tumor (studied in autopsy) and the mammary metastasis ( analyzed after surgical remo val), confirmed the gastric origin of the latter. The more remarkable points of the clinico-patrological facts of these secondary tumors are described, and emphasis is placed on the dire necessity of an early diagnosis to avoid unnecessary radical surgical removal.